Transistor audio amplifiers - Jones, Dwight V. (Jonh Wiley and sons, inc., 1968)
In 1955 the first version of Transistor Audio Amplifiers was published. It was a small book intended to illustrate the applications of these relatively new devices to audio field. Although electron tubes still largely pre-empted the field, transistors were beginning to make serious inroads, and the indication was that they would eventually take it over completely. In the years since the first vesion appeared this has in fact proved true.